Respostas

2014-07-10T12:18:29-03:00
2x²-3x²-5x+7x+3-3=0          3y³-3y³+2y²-y²+y-5y-1+3=0
-x²+2x=0 (-1)                     y²-4y+2=0
x²-2x=0                             Δ=b²-4ac
x.x-2.x=0                          Δ=4²-4.1.2
x.(x-2)=0                           Δ=16-8
x=0                                  Δ=8
x-2=0                               y=-b²+-√Δ
x=0+2                                     2a
x=2                                  y=-4²+-√8
S={0,2}                                   2.1
                                       y=16+-√8
                                              2
Obs.: +- = mais ou menos